2018
DOI: 10.30703/cije.426627
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Proportional Reasoning of Middle School 5th , 6th and 7th Grade Students according to a Two-Tier Diagnostic Test

Abstract: This paper was checked for plagiarism using iThenticate during the preview process and before publication. / Bu çalışma ön inceleme sürecinde ve yayımlanmadan önce iThenticate yazılımı ile taranmıştır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
4
0
3
Order By: Relevance
“…In the studies carried out to evaluate and develop proportional reasoning of middle school students, different solution methods used by students in ratio and proportion problems were examined, and it was also emphasized that students were able to distinguish non-proportional situations from proportional situations (Avcu & Doğan, 2014;Ayan-Civak, 2020;Ayan & Işıksal-Bostan, 2019;Mersin, 2018). To illustrate, Avcu and Doğan (2014) determined the strategies used by seventh grade students in solving proportional problems.…”
Section: Proportional Reasoningmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies carried out to evaluate and develop proportional reasoning of middle school students, different solution methods used by students in ratio and proportion problems were examined, and it was also emphasized that students were able to distinguish non-proportional situations from proportional situations (Avcu & Doğan, 2014;Ayan-Civak, 2020;Ayan & Işıksal-Bostan, 2019;Mersin, 2018). To illustrate, Avcu and Doğan (2014) determined the strategies used by seventh grade students in solving proportional problems.…”
Section: Proportional Reasoningmentioning
confidence: 99%
“…In addition, students had difficulties in using additive relations in non-proportional situations. In a study about middle school students' proportional reasoning, Mersin (2018) found that students had misconceptions concerning multiplicative and additive related variables. It was observed that the students had difficulties in determining what and when to use the relation between the variables, such as using multiplicative relations where additive relations should be used.…”
Section: Proportional Reasoningmentioning
confidence: 99%
“…Despite the mentioned advantages, Haja and Clarke (2011) pointed out that two-tier tests are not widely used in mathematics education. Indeed, when the proportional reasoning tests for middle school students are examined, two-tier tests are found in just a few studies (Haja & Clarke, 2011;Hilton et al, 2013;Mersin, 2018). Haja and Clarke (2011) aimed to evaluate middle school students' justification skills with twotier proportional reasoning tasks.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…The test consists of 12 items related to nonproportional (constant/additive), one or two-dimensional scale, missing value, familiar rate, rate, translation of representations, relative thinking, inverse proportion. Mersin (2018) mentioned that proportional reasoning measuring tools used in Turkey do not allow students to justify their answers and so she translated the two-tier proportional reasoning diagnostic test developed by Hilton et al (2013) into Turkish. Since the two-tier PRST in the literature is a limited number, and there isn't any two-tier PRST developed in Turkish, it is considered important to develop a two-tier PRST that can allow to justify their answers.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Orantısal akıl yürütmeye yönelik yapılan tanımlara bakıldığında, ilkokul ve ortaokul matematik derslerinde önemli bir kavram ve temel yapı taşı olarak ifade edilmektedir (Lamon, 2007;Lesh vd., 1988). Nitekim orantısallığı veya çarpımsal ilişkileri ayırt edebilmek kadar orantısal olmayan durumları da ayırt etmek bu akıl yürütme türünün önemli bir parçasıdır (Cramer vd., 1993;Dinç-Artut ve Pelen, 2015;Mersin, 2018;Modestou ve Gagatsis, 2008;Pelen ve Dinç-Artut, 2015;Singh, 2000;Toluk-Uçar ve Bozkuş, 2016;Van-Dooren vd., 2010). Ayrıca, yalnızca öğrencilerin değil yetişkinlerin de tüm yaşantısı boyunca oransal ilişkilerde orantısal akıl yürütmeye ihtiyaç duyduğu ifade edilmektedir (Lamon, 2012).…”
Section: Introductionunclassified